Extensive DNA sequence homologies between the human Y and the long arm of the X chromosome. - Geldwerth, D (1985)
It has been proposed that sequence homology should exist between the short arms of the human sex chromosomes, in the regions pairing at meiosis. Out of 40 clones picked at random from a collection of non-repetitive DNA sequences derived from the human Y chromosome, we have found nine sequences which show very high homology with sequences located on the X chromosome. All nine probes originate from the euchromatic part of the Y chromosome. All the homologous sequences are located within the Xq12-Xq22-24 region. None of them map to the short arm of the X chromosome. We conclude that an important part of the euchromatic region of the Y chromosome is homologous to the middle of the X chromosome long arm, possibly as a result of recent translation event(s).